TVFP : um algoritmo de entrega de mensagens para redes DTN baseado em grafos variantes no tempo - Alvarez, Álvaro Shiokawa (Universidade Federal de São Carlos, 2016)
The perspective of an accelerated growth of the Internet of Things, has been increasing the concern on how to make the infrastructure of networks more robust and energetically efficient. In this sense, opportunistic and dynamic networks, such as delay and disruption tolerant networks (DTN) and vehicular ad-hoc networks (VANET), need to be compatible with extremely efficient message routing algorithms. Examples of routing algorithms for opportunistic networks include the Epidemic and the Spray-and-Wait, which have high message transmission cost. With the objective of obtaining a more efficient communication, this work presents a new message routing approach based on dynamic graphs, known as Time-Varying Graphs (TVG). In the literature, there are algorithms which calculate optimal paths within a TVG, for example, the path which allows the minimum travel time for a message. This work proposes a distributed routing algorithm, named Time-Varying Shortest Path (TVFP), which calculates the optimal path in a TVG that allows message delivery within the shortest possible time. The algorithm was implemented in the ONE simulator and experiments were conducted in order to comparatively evaluate its performance against other DTN algorithms. The results show that TVFP has better performance than the other algorithms, delivering messages in shorter times and causing a smaller overhead due to generation of redundant and intermediate messages.
Keywords: DTN; TVG; VANET; TVFP; ONE; CIENCIAS EXATAS E DA TERRA